SIGNIFICIANCE AND EFFECTS OF GLOBALIZATION - Filipovski, Zoran; Sherifi, Qazime; Gligorova, Anita (International Scientific Journal Vision, 2022)
This paper describes the areas in which globalization as a process encompassed the globe, the pace of change and its multidimensional effect. The paper also highlights many examples of positive effects, benefits from the process of globalization in many areas, especially in the economic aspect of the international community. Globalization as a process, of course, has also met with anti-globalists, who are skeptical about the benefits of this process, but at the same time concerned. This point is elaborated in detail in the paper, starting from their point of view on globalization as a determinant of creating inequality of strata, then which countries, regions or cultures are endangered by this process in a multidimensional context, but also radical forms of opposition on their part.